Active commuting on a large university campus - Wittman, Pam (Kansas State University, 2009)
Physical activity (PA) is known to contribute to health benefits, including enhanced cardiovascular fitness, reduced chronic disease, and weight maintenance. Despite the benefits of PA, less than half of Americans meet recommendations. Recent research has shown several short bouts of exercise added up throughout the day are effective in obtaining health benefits. The purpose of this study was to understand patterns and influences of active commuting (AC) behavior. METHODS: An online study of AC patterns was conducted at a large Midwest university campus. Students, faculty, and staff answered questions about frequency of walking, biking, and driving to campus. Respondents were asked about current PA, influences on commuting habits, and geographic characteristics related to commuting. RESULTS: 835 respondents participated. 54.7% were female and 44.5% were students. Self reported distance from home to campus was the most powerful determinant of active commuting. Individuals living within a self‐reported twenty minute walk from campus walked twice as often as those living further, while those living within a twenty minute bike ride biked seventeen times more frequently than those reporting a greater distance. Students were six times more likely to actively commute. The three most influential reasons for mode of commute were: time constraints, weather, and traveling to other points before or after school. Safety from crime and traffic were positively associated with AC. Conclusion: With current economic and environmental concerns, AC should be considered a viable and sustainable behavior that can be targeted with future public health and health promotion initiatives.
Keywords: Active commuting; Physical activity; University campuses